Review of the possibilities of regional intra-arterial chemotherapy in the treatment of squamous cell carcinoma of the nasal cavity and paranasal sinuses - A. M. Mudunov; M. N. Narimanov; D. A. Safarov; B. I. Dolgushin; A. A. Akhundov; I. A. Trofimov (Опухоли головы и шеи, 2018)
In this literary review analyzed the possibilities of combination therapy in the treatment of locally advanced squamous cell carcinoma of the nasal cavity and paranasal sinuses, compares the frequency and nature of side effects in its different variants, assessed the effectiveness of intra-arterial chemotherapy in comparison with other methods.Combined treatment with the use of systemic chemotherapy allows not carry out massive surgical operations, but does not improve the long-term results of treatment. Regional intra-arterial chemotherapy has a number of advantages: improves the tumor response to treatment, long-term results, as well as expands the possibilities of organ-preserving treatment performance and, accordingly, improves the quality of life of patients. Another advantage is the possibility of a parallel use of detoxifier, which excludes the toxic effect, which is inherent in systemic chemotherapy. The implementation of this technology in a wide clinical practice is limited by the need for special equipment for interventional radiology and, consequently, the increased cost of treatment. However, the high efficiency of this method in the future is likely to lead to its active implementation in clinical practice.